(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The relevance of the study lies in the fact that in the power supply system there is a problem of choosing the parameters of the elements of the electrical network according to technical and economic indicators. The increase in the number of electricity consumers is associated with the expansion of energy consumption facilities in urban and industrial enterprises, as well as in agriculture. One of the solutions to this problem is the choice of optimal parameters of power transmission lines that provide consumers with electricity, for example, the cross-section of the surfaces of the lines at the optimal value. It is important to correctly determine the location of the transformer substation that provides electricity to the territory in combination with the cross-sectional surface of the line. Study of the factors influencing the technical and economic parameters to be selected and their mathematical expressions. A small micro districts belonging to the area of urban electricity supply was chosen as the object of the study. To determine the optimal parameters, mathematical expressions have been developed using the method of mathematical expectations and matrices in determining capital and operating costs. The results of the study showed that issues related to the establishment of permissible values of electrical load and voltage when determining the cross-sectional surfaces of lines, as well as all factors affecting the determination of terrain coordinates, can change the technical and economic value of optimal parameters. The parameters obtained as a result of solving the problems discussed in this article are used in the distribution electrical networks of the power supply system (0,4/6/10 kV), as well as during the construction of transformer substations on the territory.